Prevalence of anxiety and depression in former elite athletes: a systematic review and meta-analysis - Adam Runacres; Zoe A Marshall (BMJ Open Sport & Exercise Medicine)
Objectives To summarise the evidence regarding the prevalence of anxiety and depression in former elite athletes compared with the general population.Design Systematic review and meta-analysis.Data sources Five electronic databases (Web of Science, PubMed, MEDLINE, Scopus and SPORTDiscus) were searched from 1970 to 2023.Eligibility criteria Studies were included in the meta-analysis if they: (1) were written in English; (2) included male or female elite athletes that had been retired ≥1 year; (3) included a control group or population reference values; (4) reported the time-point prevalence of anxiety and/or depression; and (5) were of a retrospective, longitudinal or prospective, methodological design. A modified version of the Downs and Black tool was used to determine risk of bias.Results 37 unique studies including 24 732 former athletes (2% female) were included in the meta-analysis. The time-point prevalence of anxiety (prevalence ratio (PR): 2.08 (95% CI 1.57 to 2.60)) and depression (PR: 2.58 (95% CI 2.04 to 3.12)) in former athletes was over twice that of the general population. Subgroup analyses revealed former American football players and jockeys had the highest time-point prevalence of both anxiety and depression (PR: 2.24–2.88), whereas the time-point prevalence of depression and anxiety was not significantly different to the general population for former rugby players (PR: 1.13–1.30).Conclusion Our meta-analyses demonstrated the time-point prevalence of anxiety and depression in former elite athletes could be over twice that of the general population, with sport-specific differences evident.PROSPERO registration number CRD42022347359.